Analisis Faktor-Faktor Penurunan Hasil Asesmen Kompetensi Minimum (AKM) Literasi pada Siswa di SDN 58 Pangkalpinang - widya Ayu Lestari; Yuanita; Sisi Pitriyana (JBES (Journal Basic Education Skills), 2026)
The decline in Minimum Competency Assessment (AKM) literacy results among primary school students has become a serious concern, as it indicates a weakness in fundamental reading comprehension skills. This study was prompted by a two-year consecutive decline in AKM literacy outcomes at SDN 58 Pangkalpinang. The aim of this research is to analyse the internal and external factors contributing to the decline in achievement. The method used is qualitative, employing interviews, literature reviews, and observations. Data were gathered from literature sources and interviews with teachers, the school principal, and students. The data analysis technique in this study consists of three stages: data reduction, systematic data presentation, and conclusion drawing. The findings indicate that internal factors include low reading interest, weak early literacy habits, and the impact of the pandemic on students' literacy development. External factors involve limited parental involvement, the lack of reading habits at home, and the suboptimal collaboration between school and family. This study recommends the importance of synergy among teachers, schools, and parents, as well as strengthening literacy strategies to improve students’ AKM outcomes.